Ketamine-induced neurotoxicity blocked by N-Methyl-d-aspartate is mediated through activation of PKC/ERK pathway in developing hippocampal neurons. (23rd April 2018) - Jiang, Sufang; Li, Xuze; Jin, Wei; Duan, Xiaofeng; Bo, Lijun; Wu, Jiangli; Zhang, Rui; Wang, Ying; Kang, Rongtian; Huang, Lining
Highlights: Ketamine induces activation of cell cycle entry, resulting in cell cycle–related neuronal apoptosis. Ketamine administration alters early and late apoptosis of cultured hippocampus neurons by inhibiting PKC/ERK pathway. Excitatory NMDA receptor activation activates PKC/ERK pathway and reverses neuronal apoptosis induced by ketamine. Abstract: Ketamine, a non-competitive N -methyld -aspartate (NMDA) receptor antagonist, is widely used in pediatric clinical practice. However, prolonged exposure to ketamine results in widespread anesthetic neurotoxicity and long-term neurocognitive deficits. The molecular mechanisms that underlie this important event are poorly understood. We investigated effects of anesthetic ketamine on neuroapoptosis and further explored role of NMDA receptors in ketamine-induced neurotoxicity. Here we demonstrate that ketamine induces activation of cell cycle entry, resulting in cycle–related neuronal apoptosis. On the other hand, ketamine administration alters early and late apoptosis of cultured hippocampus neurons by inhibiting PKC/ERK pathway, whereas excitatory NMDA receptor activation reverses these effects. Ketamine-induced neurotoxicity blocked by NMDA is mediated through activation of PKC/ERK pathway in developing hippocampal neurons.